2004
DOI: 10.1007/s00421-004-1158-6
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in base rate measures of cardiac autonomic activity

Abstract: To investigate the role of the circadian pacemaker in autonomic modulation of base rate cardiac activity, 29 healthy subjects participated in a constant routine protocol. They were randomly divided into two groups in order to manipulate prior wakefulness. Group 1 started at 0900 hours immediately after a monitored sleep period, while group 2 started 12 h later. Measures of interbeat intervals (IBIs), respiratory sinus arrhythmia (RSA, an estimate of parasympathetic activity), pre-ejection period (PEP, an estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
0
31
2
Order By: Relevance
“…Second, measurements of HRV were obtained under paced breathing during the midday. It has been suggested that HF HRV may be enhanced by paced breathing [32], and as there is a circadian rhythm of HF HRV [33], these results may not necessarily generalize to other times of the day. Third, the two comparison groups differed in their age range, with the insomniac group having a wider age range.…”
Section: Discussionmentioning
confidence: 97%
“…Second, measurements of HRV were obtained under paced breathing during the midday. It has been suggested that HF HRV may be enhanced by paced breathing [32], and as there is a circadian rhythm of HF HRV [33], these results may not necessarily generalize to other times of the day. Third, the two comparison groups differed in their age range, with the insomniac group having a wider age range.…”
Section: Discussionmentioning
confidence: 97%
“…They identified a circadian variation in a number of variables derived from HR, but only when the protocol commenced early on day 1. If the protocol began in the evening of day 1, the circadian influence was lost, presumably obscured by sleep deprivation influences [70]. Consistent with this, one study using a forced desynchrony protocol has shown a relatively strong circadian system influence over BP (a peak to trough systolic difference of 9 mmHg) [62].…”
Section: Introductionmentioning
confidence: 92%
“…Because of the circadian rhythm of cardiac vagal activity [25], timing of HRV measurements was standardized in the afternoon. Research assistants who measured HRV were blinded to our study hypotheses.…”
Section: Methodsmentioning
confidence: 99%